PENGEMBANGAN MEDIA WORDLY CARDS BERBASIS AUGMENTED REALITY (AR) MELALUI APLIKASI ASSEMBLR EDU PADA MATERI KOSAKATA KELAS IV DI SDN - Umar, Nurfatima; Husain, Rusmin; Pulukadang, Wiwy T.; Halidu, Salma; Katili, Sukri (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Digital-based learning technology is rapidly advancing, one of which is the application of Augmented Reality (AR) in educational media. The purpose of this research is to develop Wordly Cards Based on Augmented Reality (AR) as a learning media, which are AR-based vocabulary cards designed using the Assemblr Edu application, making them suitable for use in Indonesian language learning on the topic of Loanwords. The research method used is the Research and Development method, employing the ADDIE development model, which includes Analysis, Design, Development, Implementation, and Evaluation. The analysis stage is conducted to understand user needs, followed by the design and development of cards containing AR content using the Assemblr Edu application. Implementation was carried out with a trial of the developed product. Evaluation is conducted by dividing pre-test and post-test questions to measure the effectiveness of the media. Media Wordly Cards Based on Augmented Reality (AR) as a learning medium for fourth-grade students at SDN 8 Kabila, is declared very suitable for use as a teaching medium. Based on the results of media expert validation, it received a percentage of 100% with the category